Brigadier Frederick; and, The Dean's Watch - Erckmann-Chatrian; Burton, Richard, 1861-1940 (Salt Lake City, UT : Project Gutenberg, 2015)
"Brigadier Frederick and The Dean's Watch" by Erckmann-Chatrian is a historical novel written in the late 19th century. The story centers on Father Frederick, a brigadier forester, who reflects on his life, the tranquility of his rural existence in Alsace, and the approaching storms of war that threaten his way of life. As a tale steeped in themes of love, loss, and the impact of conflict on ordinary life, it aims to impart a poignant message on the human experience amidst the backdrop of historical events. The opening of the novel introduces Father Frederick as he reminisces about his idyllic past$1 (Ba life filled with love, family, and the serenity of nature$1 (Bbefore the encroachment of war disrupts his peaceful existence. He recalls the joys of his days with his daughter, Marie-Rose, and the bonds formed with the community. However, hints of impending conflict permeate the narrative, as he poignantly acknowledges the difficulties brought by misfortunes and the looming presence of Prussian soldiers. As the plot unfolds, the reader is drawn into Frederick's internal struggles and the tumultuous changes that threaten the life he's built, setting the stage for deeper explorations of humanity and the harsh realities of war. (This is an automatically generated summary.)s
Release date is 2015-10-11
Produced by Al Haines
Keywords: French fiction -- Translations into English